The law of the origin in the ontology of consciousness: (Descartes' third meditation) - R. Buonamano (Law Text Culture, 1998)
The history of law is a history of finitude, which would be only one of the many histories of finitude, of the human condition or ontology. This irreducible point escapes those who invest all their efforts in understanding law through the scope of legitimacy how does the law come to calculate, decide, institute, pronounce and effect? By what right? On what foundation, origin, universalising pretext, does it so act? If we abandon this line of questioning, the pursuance ofwhich would only lead us through a gyre ofself-referential dilemmas circumventing the concept of 'origin', it becomes dear that it is precisely the role of the origin in its law-configuring mode that problematises what law can and does do, that is to say, what law is. But, even having isolated this theoretical agenda, there are no obvious signposts to navigate one's journey into this 'law-configuring origin'.